Medical Student Spirituality and Substance Use. Issue 6 (December 2020) - Williams, Michelle K.; Greene, William M.; Leitner, Stefano A.; Merlo, Lisa J.
Abstract : Objectives: Although medical students report relatively high levels of substance use, little is known about the risk and protective factors associated with substance use in this population. This study sought to examine the link between spirituality and substance use among medical students. Methods: As part of a larger study, medical students from all 9 medical schools in the state of Florida were invited to complete an anonymous survey pertaining to distress and well-being. Responses to items assessing self-reported spirituality and substance use were examined and descriptive statistics were analyzed. Results: Data from 868 medical students (57% female) were included. Of these, 22.6% described themselves as "non-spiritual, " 31.0% described themselves as "spiritual, " 18.5% engaged in informal spiritual practices, and 27.9% reported formal spiritual/religious practices. Students who reported stronger spirituality also reported lower rates of substance use. Though 31% of respondents across all levels of spirituality reported that their alcohol consumption increased since starting medical school, rates of binge drinking after exams were inversely related to level of spirituality. Conclusions: Self-reported spirituality appears to be associated with decreased risk of substance use in medical school. Future studies should examine this relation in greater depth.